2019
DOI: 10.1371/journal.pone.0210364
|View full text |Cite
|
Sign up to set email alerts
|

The effect of local land use on aerial insectivorous bats (Chiroptera) within the two dominating crop types in the Northern-Caribbean lowlands of Costa Rica

Abstract: Land transformation into agricultural areas and the intensification of management practices represent two of the most devastating threats to biodiversity worldwide. Within this study, we investigated the effect of intensively managed agroecosystems on bat activity and species composition within two focal areas differing in landscape structure. We sampled bats via acoustic monitoring and insects with flight interception traps in banana and pineapple monoculture plantations and two nearby protected forested area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Together, this could explain the absence of some of the forest insectivores in the forest samples; in future studies, lower detection rates in forest habitat could be resolved by adding recording devices in the canopy. What is noteworthy, however, is the high detection of those forest specialist species in the restoration sites, a phenomenon that has been observed in other open habitats (banana and pineapple plantations; Alpízar et al, 2019). Assessing community composition of the aerial insectivore assemblage demonstrated that more species were associated with restoration habitat than expected, including those species that are forest foragers.…”
Section: Discussionmentioning
confidence: 89%
“…Together, this could explain the absence of some of the forest insectivores in the forest samples; in future studies, lower detection rates in forest habitat could be resolved by adding recording devices in the canopy. What is noteworthy, however, is the high detection of those forest specialist species in the restoration sites, a phenomenon that has been observed in other open habitats (banana and pineapple plantations; Alpízar et al, 2019). Assessing community composition of the aerial insectivore assemblage demonstrated that more species were associated with restoration habitat than expected, including those species that are forest foragers.…”
Section: Discussionmentioning
confidence: 89%
“…However, the records of occurrence are often from limited areas and are completely lacking from western Nepal. Our predictions of changes in ranges and elevations were modeled on the basis of 19 bioclimatic variables, however vegetation, land use, and disturbance also affect the distributions of bats (Alpízar et al., 2019; de Oliveira et al., 2017). Furthermore, habitat‐specific species of bats may suffer more from the changing climate, for example due to increased risk of interspecific competition from commoner species expanding their ranges (Colles et al., 2009; Thapa, Baral, et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Artificial light at night has been increasing over time in biodiversity hotspots (Guetté et al., 2018) and this is concerning because the increasing human pressure in the periphery of forested areas can leave forest fragments in a state of constant illumination during the night. Although artificial light attracts insects consumed by insectivorous bats, some bat species studied here are sensitive to urbanization (Alpízar, Rodríguez‐Herrera, and Jung, 2019; Jung and Kalko, 2010). It is known that lit areas can influence the quality of roosts and fragment commuting routes for some bat species with negative consequences for the reproduction and behaviour of bats (Downs et al., 2003; Laforge et al., 2019; Straka et al., 2019).…”
Section: Conservation Implicationsmentioning
confidence: 99%